MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MELUKIS DENGAN TEHNIK PINGER PAINTING DI TK NEGERI I PEMBINA MEDAN - Rahmi Bachtar (Universitas Negeri Medan, 2019)
The purpose of this class action research is to improve the fine motor skills of children through painting activities using the technique of pinger paenting in the BTK class of Pembina 1 Medan, Jln. Ujung Karya Medan City. The subjects in this class action research were class B kindergarten children which numbered 15 people consisting of 9 female students and 6 male students. The data collection technique used in this study is to use quantitative data in the form of tests and qualitative data in the form of observations. The observation shows that in the first cycle the teacher (researcher) has been able to improve the fine motor skills of the child by painting with the pinger paeting technique in fine motor learning activities well (35%) and in cycle II the teacher (researcher) can apply to improve fine motor skills in painting with the technique of pinger paenting very well (80%). In the first cycle students 'activities were classified into sufficient categories, while in the second cycle students' activities increased and were classified in the good category. Keywords: Fine motoric children, Painting, pinger technique paenting